In schizophrenia, psychomotor retardation is associated with executive and memory impairments, negative and psychotic symptoms, neurotoxic immune products and lower natural IgM to malondialdehyde. (27th May 2020) - Maes, Michael; Sirivichayakul, Sunee; Kanchanatawan, Buranee; Carvalho, André F.
Abstract: Objectives: Stable-phase schizophrenia comprises two distinct entities namely Major Neuro-Cognitive Psychosis (MNP) and simple NP (SNP), which are defined by neuroimmune and neurocognitive abnormalities. Methods: This study investigates associations of psychomotor retardation (PMR), clinical and biomarker characteristics of schizophrenia. We recruited 40 healthy controls and 79 schizophrenia patients and measured IgA responses to tryptophan catabolites (TRYCATs), IgM to malondialdehyde and nitroso (NO)-cysteinyl, CCL-11, an immune activation index based on cytokine levels, and motor screening task (MOT) scores. Results: PMR differentiated schizophrenia from controls and MNP from SNP. In addition, PMR was strongly associated with impairments in executive functions and episodic and semantic memory, psychotic, hostility, excitation, mannerism and negative (PHEMN) symptoms. Around 50% of the variance in PMR was predicted by the cumulative effects of the immune activation index, CCL-11, TRYCATs, NO-Cysteinyl and natural IgM. PRM can reliably be combined with PHEMN symptoms, memory and executive impairments into one latent vector reflecting overall severity of schizophrenia. Conclusions: PMR is a key psychopathological feature of schizophrenia mainly MNP. In addition, PMR may be driven by deficits in the compensatory immune-regulatory system and increased production of neurotoxic immune products, namely TRYCATs, IgM to NO-cysteinyl, and CCL-11, an endogenous cognition deteriorating chemokine.